2006
DOI: 10.4028/www.scientific.net/kem.317-318.389
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Resistance of Commercial Si<sub>3</sub>N<sub>4</sub> Bearing Balls

Abstract: The corrosion rate (Cr) of commercially available ball bearings made of silicon nitride (Si3N4) of high degree (HD) and standard quality (S) was measured at hydrothermal conditions in different aqueous concentrations of sulphuric acid (H2SO4) and sodium hydroxide (NaOH). The Cr magnitude for the materials diminished when increasing the acid concentration. At higher concentrations of H2SO4 (98%) the formation of SiO2 on the surface of the balls inhibited the progress of corrosion. The corrosion rate of the mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Previous authors have observed pitting in investigations of hot-pressed Si 3 N 4 in acidic or alkaline conditions and in studies of pressureless sintered Si 3 N 4 [12,15,31], but rarely has the pitting mechanism been seen as a result of hydrothermal tests. Electron microscopy and EDS of pitting observed in the ‘A’ samples revealed titanium-rich inclusions located in many of the pits (Figure 6), suggesting that the titanium additive promotes localised pitting corrosion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have observed pitting in investigations of hot-pressed Si 3 N 4 in acidic or alkaline conditions and in studies of pressureless sintered Si 3 N 4 [12,15,31], but rarely has the pitting mechanism been seen as a result of hydrothermal tests. Electron microscopy and EDS of pitting observed in the ‘A’ samples revealed titanium-rich inclusions located in many of the pits (Figure 6), suggesting that the titanium additive promotes localised pitting corrosion.…”
Section: Discussionmentioning
confidence: 99%
“…In aeroengine bearings which usually endure high-speed, high-temperature and heavy-load environments [1,2], silicon nitride (Si 3 N 4 ) ceramic balls have been widely used due to the high hardness, low density, excellent wear resistance, and thermal stability [3-5]. Furthermore, the use of diamond-like carbon (DLC) films on Si 3 N 4 surfaces is an effective approach for improving the tribological properties of Si 3 N 4 [6,7].…”
Section: Introductionmentioning
confidence: 99%